Синтез модельно-прогнозуючого регулятора режиму дуття кисневоконвертерного процесу - Степанець, Олександр Васильович; Маріяш, Юрій Ігорович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Мета дослідження полягає у знижені собівартості киснево-конвертерної сталі, що є наслідком підвищення частки металобрухту за рахунок підвищення ступеня допалювання СО до СО₂ в порожнині конвертера, шляхом оптимального керування параметрами дуттєвого режиму з використанням модельно-прогнозуючого керування. Синтезовано оптимальну систему керування параметрами дуттєвого режиму киснево-конвертерної плавки за принципом зворотного зв’язку на базі модельно-прогнозуючого керування при використанні лінійно-квадратичного функціоналу.

The purpose of the research was to find a solution for a decrease in the cost price of the basic oxygen furnace steel. It is conditioned by an increase in the scrap metal portion due to an increase in the СО to CO₂ afterburn degree in the basic oxygen furnace cavity according to the optimal model predictive control of the parameters of the blowing mode. The optimal parameter control system was synthesized for the blowing mode of the oxygen-converter melting on the basis of the feedback based on the model-predictive control using the linear-quadratic functional and it enabled a simultaneous control of the blowing intensity and the lance position when programmatically changing the task for the oxygen consumption and CO₂ content improving also the control quality and energy saving during the melting process due to an increased afterburn degree during the CO to CO₂ conversion that is a consequence of an increased portion of the scrap metal. Closed CO to CO₂ afterburn degree control systems were improved by the synthesis of the model-predictive controller taking into consideration process limitations imposed on the shifting rate of controlling mechanisms, improving thus the process control quality in the case of the limitations. The suggested solution enables certain process control quality improvement under the conditions of process limitations. A comparative investigation of the operation of the model – predictive controller and combined control system with PID–controllers showed that the obtained transition processes of the automatic control of the blowing mode for the basic oxygen furnace melting using the automatic model-predictive controller provided ISE values for the oxygen consumption loop equal to 5577 and the CO₂ content equal to 43 in basic oxygen furnace gases with a maximum dynamic deviation of the CO₂ content in converter gases equal to 0.95 %. The use of the model-predictive controller allowed us to improve the control quality for the oxygen consumption loop by a factor of 1.63 CO₂ and by a factor of 32.5 for the CO₂ content control loop in converter gases. A maximum dynamic deviation of the CO₂ content in converter gases was reduced by 16.55 % in comparison to that in the combined control system equipped with PID-controllers.
Model-predictive blowing mode controller synthesis for the oxygen-converter process
Keywords: модельно-прогнозуюче керування; оптимальне керування; модель в просторі станів; лінійно-квадратичний функціонал; киснево-конвертерний процес; model-predictive control; optimal control; state-space model; linear-quadratic functional; basic oxygen furnace